Sistem Penjualan Sembako Toko Sarwodadi - Nugroho, Fajar (Jurnal Teknologi dan Bisnis, 2021)
The structure of data processing and information systems that are still manual at the dc Sarwodadi store make the system run ineffective, so this causes various problems. Another problem is the system of selling, purchasing, ordering goods, and stocking goods which are still difficult to organize, causing errors in counting. For this reason, a sales application system was made which aims to manage and process data stored with a database system to prevent data redundancy causing losses to the store. This research method uses the SDLC method. The SDLC method is a method with the process of system development and design to operation and maintenance. Data storage using MySQL type database. The Sarwodadi dc Store Sales Application System has data processing facilities for purchasing, selling, ordering goods, and stocking goods along with report data. So that with the new system, 83.3% of participants stated that the whole system was feasible and good to use in helping the Sarwodadi store to process data, make reports, and make it easier to get information about processed data both for the Sarwodadi store it self